2001
DOI: 10.1126/science.1060818
|View full text |Cite
|
Sign up to set email alerts
|

Impulsive Choice Induced in Rats by Lesions of the Nucleus Accumbens Core

Abstract: Impulsive choice is exemplified by choosing a small or poor reward that is available immediately, in preference to a larger but delayed reward. Impulsive choice contributes to drug addiction, attention-deficit/hyperactivity disorder, mania, and personality disorders, but its neuroanatomical basis is unclear. Here, we show that selective lesions of the nucleus accumbens core induce persistent impulsive choice in rats. In contrast, damage to two of its afferents, the anterior cingulate cortex and medial prefront… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

58
635
11
6

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 809 publications
(714 citation statements)
references
References 30 publications
58
635
11
6
Order By: Relevance
“…Previous work involving drug or lesion studies suggests that lower levels of 5-HT and DA are related to increased impulsive choice or increased rates of delay discounting (Evenden, 1999b;Cardinal et al, 2000Cardinal et al, , 2001Harrison et al, 1997;Mobini et al, 2000;Wogar et al, 1993). Such neurochemical effects may contribute to the present outcome as Lewis rats have been shown to have lower levels of 5-HT and DA in various brain regions relative to Fisher 344 rats (Selim and Bradberry, 1996;Lindley et al, 1999).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous work involving drug or lesion studies suggests that lower levels of 5-HT and DA are related to increased impulsive choice or increased rates of delay discounting (Evenden, 1999b;Cardinal et al, 2000Cardinal et al, , 2001Harrison et al, 1997;Mobini et al, 2000;Wogar et al, 1993). Such neurochemical effects may contribute to the present outcome as Lewis rats have been shown to have lower levels of 5-HT and DA in various brain regions relative to Fisher 344 rats (Selim and Bradberry, 1996;Lindley et al, 1999).…”
Section: Discussionmentioning
confidence: 92%
“…Reporting data in this way is consistent with other published studies (cf. Ryan, 1996, 1999;Cardinal et al, 2000Cardinal et al, , 2001) and thus, allows for comparisons among studies that have used the same or similar procedure. Statistical analysis of the data (repeated-measure ANOVA) were used to assess differences between the groups during baseline and drug treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that the NAC, well innervated by DA neurons, plays an important role in impulsive choice in rats (Cardinal et al, 2001). Aggressive and impulsive behaviors in rodents are modulated, in part, by DA activity at D1 and D2 receptors (Harrison et al, 1997;Vukhac et al, 2001).…”
Section: Da Dysfunction and Impulsive Behaviors In Animalsmentioning
confidence: 99%
“…It has been shown that the anterior cingulate cortex [17] and ventral striatum [12] and their dopaminergic innervation [7,14] may be critically involved in choices encompassing barriers as effort. The anterior cingulate cortex is not involved in choice behaviour based on delays as effort, whereas the ventral striatum is [4], although data from recent studies tend to suggest otherwise with respect to (dopamine in) the ventral striatum [9,16]. Thus far it has been shown that (the prelimbic and infralimbic areas of) the medial prefrontal cortex [4,5] and orbitofrontal cortex [10,18] are sensitive to choices involving delays.…”
mentioning
confidence: 99%
“…The anterior cingulate cortex is not involved in choice behaviour based on delays as effort, whereas the ventral striatum is [4], although data from recent studies tend to suggest otherwise with respect to (dopamine in) the ventral striatum [9,16]. Thus far it has been shown that (the prelimbic and infralimbic areas of) the medial prefrontal cortex [4,5] and orbitofrontal cortex [10,18] are sensitive to choices involving delays. Furthermore dopamine plays a role in choice behaviour based on delays, whereas serotonin is involved in choice behaviour based upon delays but not barriers [7].…”
mentioning
confidence: 99%